Menumbuhkan Jiwa Wirausaha Melalui Peran Sosial Media - Indoworo, Hawik Ervina (JIU, 2016)
Abstract - Now the development of entrepreneurship is able to expand new employment opportunities and sustain the economy of the State. The need for information and personal development is increasing along with advances in telecommunications technology over the internet. The development of the internet makes the number of the users taking advantage of this as a profitable business opportunity like online businesses. The euphoria of the use of social media (facebook, twitter, instagram, etc.) over the internet has become a trend in society. Of course it affects the behavior change in the way the community communicate and interact with others. This condition is driven by two fundamentals which are the new behavior of the citizen and the technological revolution. The growth of social media users should certainly benefit companies in reaching consumers with a way to innovate in doing business, marketing and communication. Keywords: entrepreneurship, social media